Phytoremediation of Soils Contaminated with Cadmium by Agave americana. Issue 13 (1st December 2022) - Ramana, Sivakoti; Tripathi, Awadhesh Kumar; Kumar, Ajay; Dey, Pradip; Saha, Jayanta Kumar; Patra, Ashok K
ABSTRACT: Agave americana was evaluated for its phytoremediation potential of the soils contaminated with Cd. This plant was selected because of its drought tolerance and high biomass. The pot culture experiment was carried with five levels of cadmium (0, 25, 50, 100, and 200 mg Cd kg soil −1 ). Parameters, viz. uptake, translocation factor (TF), translocation efficiency (TE), bioconcentration factor (BCF), etc., were calculated to study the phytoremediation potential. The study indicated that the plant was highly tolerant to Cd at lower levels, i.e., up to 50 mg Cd kg soil −1, but there was a significant reduction in dry weight of root, leaf, and total at higher levels of, i.e., , 100 and 200 mg Cd kg soil −1 . Cd mainly accumulated in the roots, and exclusion was found to be the principal physiological tolerance mechanism. Based on the tissue concentration of Cd (<100 μg g −1 in the leaves; and TF and BCF <1), A. americana was classified as an excluder of Cd. However, since, the plant could establish an evergreen cover over the contaminated/polluted land surface because of its exponential reproductive capacity, it could be suitable for the phytostabilization of soils contaminated with Cd.